PERAN PEMERINTAH DAERAH DALAM PEMBANGUNAN RUANG TERBUKA HIJAU (RTH) DI KELURAHAN PEMATANG REBA KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Winda Amelia Vada; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Green Open Space (RTH) itself can be interpreted part of open spaces (open spaces) an urban area that is filled with plants and crops to support the direct or indirect benefits generated by RTH for safety, comfort, well-being, and the beauty of urban areas .RTH which drafted by the Department of Public Works in the Village Pematang Reba namely 1) the city park; 2) park along the road; 3) Playgrounds; and 4) recreational park.From the research that the authors concluded that the implementation process of development in the Village Green Open Space District of Causeway Reba West Rengat Indragiri Hulu uses four stages: planning concepts are pretty good, but the concept of setting, implementation; and supervision has not been sufficiently well implemented, the government plays a role in the implementation process of development of green open space (RTH) in Kalurahan Pematan Reba District of West Regat Indragiri Hulu is the physical implementation delegated to the Department of Public Works in the field of Human Settlements, while the role of Local Government in the allocator budget, proposed, designed by the respective agencies appointed to carry out the activities carried out by the implementing activity Unit (SKPD).keywords: Green Open Space (RTH), Government Management, Role of Government.